The LCLS variable‐energy hard X‐ray single‐shot spectrometer. (1st January 2016) - Rich, David; Zhu, Diling; Turner, James; Zhang, Dehong; Hill, Bruce; Feng, Yiping
Abstract : The engineering design, implementation, operation and performance of the new variable‐energy hard X‐ray single‐shot spectrometer (HXSSS) for the LCLS free‐electron laser (FEL) are reported. The HXSSS system is based on a cylindrically bent Si thin crystal for dispersing the incident polychromatic FEL beam. A spatially resolved detector system consisting of a Ce:YAG X‐ray scintillator screen, an optical imaging system and a low‐noise pixelated optical camera is used to record the spectrograph. The HXSSS provides single‐shot spectrum measurements for users whose experiments depend critically on the knowledge of the self‐amplified spontaneous emission FEL spectrum. It also helps accelerator physicists for the continuing studies and optimization of self‐seeding, various improved mechanisms for lasing mechanisms, and FEL performance improvements. The designed operating energy range of the HXSSS is from 4 to 20 keV, with the spectral range of order larger than 2% and a spectral resolution of 2 × 10 −5 or better. Those performance goals have all been achieved during the commissioning of the HXSSS.